Sex ratio and size class of Trichopsis vittata in North Sumatra Province - Sonia Ayu Indah Putri; Khairul; Hasmi Syahputra Harahap (JURNAL BIOS LOGOS, 2025)
Sumatra Island, especially North Sumatra Province, is a habitat for various freshwater fish species, including Trichopsis vittata. This study aimed to assess the sex ratio and size class distribution of T. vittata in three different locations: Tebing Linggahara Village, Bulungihit Village, and Silau Rakyat Village. Fish samples were caught using a serving hood, and total length and weight were measured. The results showed that the sex ratio of T. vittata was 1:1, indicating a balance of males and females in the population. The size distribution of fish was dominated by the rather large (46.27-52.27 mm) and small (34.25-40.25 mm) classes, indicating a diverse population growth. This condition shows that the recruitment process is still running well in nature. This study is expected to be the basis for the management and conservation of T. vittata in North Sumatra waters. It is recommended that further research be conducted on the ecological aspects of the habitat to support the conservation of this species